Choroidal dendritic cells require activation to present antigen and resident choroidal macrophages potentiate this response. Issue 3 (17th February 2005) - Forrester, J V; Lumsden, L; Duncan, L; Dick, A D
Abstract : Background/aim: The uveal compartment of the eye contains extensive networks of resident macrophages and dendritic cells. These cells are now recognised to have a role in many ocular pathologies. The aim of this study was to isolate, characterise, and compare the function of ciliary body/choroid dendritic cells and macrophages from the normal eye. Methods: Explants of rat and human ciliary body/choroid were cultured in vitro for various periods of time and cells harvested either from the supernatant fluid or from enzyme digested and washed explants. The cells were then phenotyped by microscopy and flow cytometry, examined by video time lapse photomicroscopy, and analysed functionally in a series of immunoassays. Results: Two main types of dendritic cell were identified: large veil-like MHC class II mid motile but relatively non-translocatory cells and small MHC class II hi motile and rapidly translocating cells. Tissue macrophages mainly remained associated with the explants in culture but gradually lost their resident tissue marker (ED2) and detached from the explants as clusters of low density, large, CR3 (ED7) + cells, some of which underwent apoptosis. Video time lapse studies showed dendritic cells constantly interacting with large single cells and cell clusters by traversing the interstices of the cell clusters. In functional studies, freshly isolated dendritic cells were poor presenters of antigen and required activation by short term culture for acquisition of antigen presenting function. In contrast, dendritic cell depleted choroidal cell preparations containing macrophages and other cells failed to present antigen even after short term culture but augmented the antigen presenting function of dendritic cells when tested in co-culture. Conclusion: At least two types of dendritic cells are present in the normal ciliary body/choroid layer of the eye. It is likely that these cells have different functions based on their motility and potential to migrate to secondary lymphoid tissue either during normal physiological homeostatic processes or during an inflammatory response. The behaviour of resident tissue myeloid cells may decide the outcome of the organism's response to stress, foreign antigen, and ageing processes such as age related macular degeneration.